An integrative taxonomic study of north temperate Cotesia Cameron (Hymenoptera, Braconidae, Microgastrinae) that form silken cocoon balls, with the description of a new species - Vladimir Žikić; Milana Mitrović; Saša S. Stanković; José L. Fernández-Triana; Maja Lazarević; Kees van Achterberg; Dawid Marczak; Marijana Ilić Milošević; Mark R. Shaw (Journal of Hymenoptera Research, 2024)
Using CO1 sequence analysis, we investigated the relationships of Western Palearctic and Nearctic Cotesia that spin aggregated cocoons in the shape of a ball, and as adults are morphologically very similar. The analysis included the conceptual taxa C. tibialis, C. ofella, C. vanessae, C. ruficrus, C. xylina and C. yakutatensis, as well as the newly described species C. trivaliae sp. nov. The examined specimens of C. tibialis, C. ofella, C. vanessae, C. ruficrus and C. trivaliae sp. nov. were collected in several European countries, and C. xylina and C. yakutatensis in Canada and the USA. Molecular analyses showed that C. ruficrus is not closely related to the other studied taxa. Based on the genetic distances as well as biology and morphology, C. vanessae and C. ofella are confirmed as solid taxa. The species C. yakutatensis comprises two entities. Having 8 haplotypes, C. tibialis also emerges as a species complex, divided into two clusters. With 26 detected haplotypes, C. xylina shows the highest diversity, being composed of three segregates. The conceptual species C. tibialis, C. xylina and C. yakutatensis seem to be species complexes containing several candidates for recognition as distinct species. One from the European C. tibialis complex is here described as new, and the impediments to be overcome before the description of further species are outlined.